2012
DOI: 10.1523/jneurosci.0907-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Oxidative Modification and Inactivation of Mitochondrial Complex I in Epileptogenesis

Abstract: Mitochondrial oxidative stress and damage have been implicated in the etiology of temporal lobe epilepsy, but whether or not they have a functional impact on mitochondrial processes during epilepsy development (epileptogenesis) is unknown. One consequence of increased steady-state mitochondrial reactive oxygen species levels is protein post-translational modification (PTM). We hypothesize that complex I (CI), a protein complex of the mitochondrial electron transport chain, is a target for oxidant-induced PTMs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 51 publications
(60 reference statements)
6
76
0
1
Order By: Relevance
“…The ZRank scoring function was used to calculate the interaction energies of the resulting predicted protein complexes and represents a combination of van der Waals attractive and repulsive energies, short and long range repulsive and attractive energies, and desolvation 24. Similarity of the predicted protein complexes to the crystal structure (1FZB) was determined by calculating the root mean square deviation (RMSD) using the crystal structure as the reference 25. The three poses with the lowest RMSD values (ie, the greatest similarity to the crystal structure) were selected from each group for the energy comparison.…”
Section: Methodsmentioning
confidence: 99%
“…The ZRank scoring function was used to calculate the interaction energies of the resulting predicted protein complexes and represents a combination of van der Waals attractive and repulsive energies, short and long range repulsive and attractive energies, and desolvation 24. Similarity of the predicted protein complexes to the crystal structure (1FZB) was determined by calculating the root mean square deviation (RMSD) using the crystal structure as the reference 25. The three poses with the lowest RMSD values (ie, the greatest similarity to the crystal structure) were selected from each group for the energy comparison.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described ROS and consequent peroxynitrite formation can contribute to cell death though lipid peroxidation, inactivation of enzymes, mPTP opening and DNA damage. Moreover, ROS can directly inhibit mitochondrial complex 1 activity, further impeding ATP production [85,86]. ROS induced DNA damage can lead to activation of poly (ADP-ribose) polymerase (PARP), a repair enzyme.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…In studies of patients with TLE, the role of mitochondria has been suggested by inhibition of complex I of the electron transport chain (ETC) and reduction in N-acetyl aspartate levels in the hippocampus (Kunz et al, 2000; Vielhaber et al, 2008). Recent work from our group has shown increases in production of mitochondrial ROS, reactive nitrogen species (RNS), oxidative damage to oxidant-sensitive mitochondrial proteins (aconitase and complex I) and glutathione depletion in animal models of TLE (Jarrett et al, 2008; Waldbaum et al, 2010; Ryan et al, 2012, 2013). Increased mitochondrial ROS and oxidative damage to ETC enzymes suggests that mitochondrial respiration may be impaired in TLE.…”
Section: Introductionmentioning
confidence: 99%